Postoperative long-term survival of non-small cell lung cancer patients with skip-N2 metastases. (September 2021) - Schlachtenberger, Georg; Doerr, Fabian; Menghesha, Hruy; Heldwein, Matthias B.; Hagmeyer, Lars; Michel, Maximilian; Schaefer, Stephan C.; Wahlers, Thorsten; Hekmat, Khosro
Abstract: Objective: Radical lymphadenectomy is crucial in operations for non-small cell lung cancer (NSCLC). Usually pN1 and pN2 lymph nodes are affected consecutively (N1N2). Nevertheless, pN2 metastases may also occur in the absence of pN1 as skip-N2 metastases (N0N2). Here we compare the long-term survival of N1N2- and N0N2 patients. Materials and methods: 464 patients underwent surgery for NSCLC at our institution between 2012 and 2017. We retrospectively reviewed data of pN2 stage patients (n = 68). Patients with N1N2 (n = 39) were compared to N0N2 (n = 29) patients. 1-, 3-and 5-year survival rates were measured. Survival was assessed by Kaplan-Meier curves and the cox proportional hazards model was used to identify prognostic factors for overall survival. All patients received adjuvant chemoradiation therapy according to European guidelines. Results: The baseline characteristics did not differ between groups. We observed no differences in the histology, localization, or gender in our cohort. N0N2 patients showed significantly better 1- (N1N2: 82.4% vs. N0N2 100%; p = 0.001), 3- (14.7% vs. 63.6%; p=<0.001) and 5-year (9.4% vs. 43.8%; p = 0.001) survival rates. Tumor size (Hazard ratio (HR) 1.46, Confidence interval (CI 95%) 1.03–2.04; p = 0.03) and the occurrence of N1N2 (HR 4.26, CI 2.04–8.91; p < 0.0001) were independent prognostic factors for worse long-term survival. The Kaplan-Meier curves showed a reduced overall survival for N1N2 patients (log-rank N1N2, N0N2 p < 0.0001). Conclusion: N1N2 patients have a significantly worse prognosis compared to N0N2 patients. This will aid to classify the heterogeneous pN2-NSCLC patient population more precisely. Further, multimodal therapy should be considered for N1N2 patients. Highlights: Lymphadenectomy during surgical resection of NSCLC is a crucial in thoracic surgery. Usually N1 and N2 lymph nodes are affected consecutively as continuous-N2 metastases. In 20% of patients N2 metastases occur without N1 metastases as skip-N2 metastases. Patients with skip-N2 metastases have a better survival compared to continuous-N2. PN2 NSCLC is heterogeneous and could benefit from a more precise classification.